Adsorption of the natural protein surfactant Rsn-2 onto liquid interfaces. Issue 12 (14th March 2017) - Brandani, Giovanni B.; Vance, Steven J.; Schor, Marieke; Cooper, Alan; Kennedy, Malcolm W.; Smith, Brian O.; MacPhee, Cait E.; Cheung, David L.
Abstract : Using simulation and experiment we investigated the interfacial adsorption of the novel protein surfactant Rsn-2, unveiling the role of its flexible termini in this process. Abstract : To stabilize foams, droplets and films at liquid interfaces a range of protein biosurfactants have evolved in nature. Compared to synthetic surfactants, these combine surface activity with biocompatibility and low solution aggregation. One recently studied example is Rsn-2, a component of the foam nest of the frog Engystomops pustulosus, which has been predicted to undergo a clamshell-like opening transition at the air–water interface. Using atomistic molecular dynamics simulations and surface tension measurements we study the adsorption of Rsn-2 onto air–water and cyclohexane–water interfaces. The protein adsorbs readily at both interfaces, with adsorption mediated by the hydrophobic N-terminus. At the cyclohexane–water interface the clamshell opens, due to the favourable interaction between hydrophobic residues and cyclohexane molecules and the penetration of cyclohexane molecules into the protein core. Simulations of deletion mutants showed that removal of the N-terminus inhibits interfacial adsorption, which is consistent with the surface tension measurements. Deletion of the hydrophilic C-terminus also affects adsorption, suggesting that this plays a role in orienting the protein at the interface. The characterisation of the interfacial behaviour gives insight into the factors that control the interfacial adsorption of proteins, which may inform new applications of this and similar proteins in areas including drug delivery and food technology and may also be used in the design of synthetic molecules showing similar changes in conformation at interfaces.